An Exploratory Analysis of Market Segmentation and Young Mobile Phone Consumers in Nigeria - Chinwendu, Okonkwo Deborah (International Journal of Marketing Research Innovation, 2018)
Purpose - The subject of market segmentation with respect to the use of mobile phones is an area that offers promising insights to strategic marketing decisions. The principles of market segmentation as established and grounded in marketing theory contain a multi-dimensional task of segmenting, targeting and positioning. Since telecommunications has inevitably transformed the entire well – being of man, of whom the young people are an interesting category, there has been a rising interest on various patterns of mobile phone usages among young consumers. This study therefore focuses on identifying various segments inherent within the younger consumers’ category in order to aid the formulation and implementation of adequate strategic marketing decisions. Design/methodology/approach - This study adopts the exploratory research approach as it attempts to get a general grasp of issues revolving around target market segmentation, as it relates to mobile phone usage patterns among young consumers. Secondary data was used and analysed vis-à-vis the outcome of a segmentation exercise previously conducted by a field expert. Findings - This study has adapted the six very important segments inherent among young mobile phone users vis: ‘talk n texters’, ‘gaming youths’, ‘talkative trendies’, ‘aspiring to be accepted’, ‘sophisticated careerists’, and ‘international business users’ and practically related them to the Nigerian younger consumers context. Practical Implications - The implication of this study for marketing practice is that organizational decisions are better guided as it becomes a lot easier to make target marketing decisions. Besides, the differing characteristics among the young mobile phone users category have been made more visible, necessitating the design of a more focused product offering suitable to each consumer category. Originality/Value – This study is a unique effort directed at an area of concern in marketing with very little or no attention accorded to it within the Nigerian market. It captures an interesting segment of the Nigerian mobile technologies market and presents a framework that offers a good basis for much more complex research activities in the nearest future.